Working with victims: psychological assessment of victims - Siri, Mauro (Victimology, 2022)
The assessment of the victim is an important aspect of investigation, which includes medical, psychological, legal and forensic aspects. The current chapter focuses on the psychological assessment of the victims. The first part of the chapter focuses on the biopsychosocial impacts of stress and trauma while considering the field of victimology and emphasized the theoretical-practical considerations. The second part of the chapter focuses on the various psychological tests used for the evaluations with detailed descriptions of each test. It was concluded that a comprehensive psychological assessment is required for the victims by a trained psychologist who has expertise in dealing with victims to give a clear picture of the psychological process of the victims.